Globalization of national surgical, obstetric and anesthesia plans: the critical link between health policy and action in global surgery - Truché, Paul (Global Health, 2020)
Efforts from the developed world to improve surgical, anesthesia and obstetric care in low- and middle-income countries have evolved from a primarily volunteer mission trip model to a sustainable health system strengthening approach as private and public stakeholders recognize the enormous health toll and financial burden of surgical disease. The National Surgical, Obstetric and Anesthesia Plan (NSOAP) has been developed as a policy strategy for countries to address, in part, the health burden of diseases amenable to surgical care, but these plans have not developed in isolation. The NSOAP has become a phenomenon of globalization as a broad range of partners – individuals and institutions – help in both NSOAP formulation, implementation and financing. As the nexus between policy and action in the field of global surgery, the NSOAP reflects a special commitment by state actors to make progress on global goals such as Universal Health Coverage and the United Nations Sustainable Development Goals. This requires a continued global commitment involving genuine partnerships that embrace the collective strengths of both national and global actors to deliver sustained, safe and affordable high-quality surgical care for all poor, rural and marginalized people.